Perlindungan Hukum terhadap Pekerja dari Upaya Pemutusan Hubungan Kerja Sepihak - Jingga, Adinda Zhara; Febriansyah, Achmad; Turang, Yohanes Ricky; Rizki, Reza Nur; Simorangkir, Julius Caesar T (DPPM Universitas Pelita Bangsa, 2025)
This research aims to analyze the legal aspects of unilateral termination of employment disguised as voluntary resignation. The study employs a normative juridical method with statute and case approaches, examining relevant laws, legal literature, and court decisions. The findings reveal that the company's practice of forcing workers to sign resignation letters constitutes constructive dismissal, violating Articles 151, 156, and 162 of Law Number 13 of 2003 concerning Manpower in conjunction with the Job Creation Law. Such actions result in the loss of workers' normative rights, including severance pay, holiday allowance, and social security benefits. Based on legal protection theory and justice theory, these actions are legally invalid as they contradict the principles of fairness and legal certainty. The research concludes that strengthening labor supervision and workers' legal awareness is necessary to ensure effective protection against disguised dismissals in the industrial sector, alongside clear legal mechanisms through Industrial Relations Courts